2018
DOI: 10.1136/bmjopen-2018-024120
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Modified Early Warning Score generated in a Chinese emergency department: a prospective cohort study

Abstract: ObjectivesThis study aimed to validate the performance of the Modified Early Warning Score (MEWS) in a Chinese emergency department and to determine the best cut-off value for in-hospital mortality prediction.DesignA prospective, single-centred observational cohort study.SettingThis study was conducted at a tertiary hospital in South China.ParticipantsA total of 383 patients aged 18 years or older who presented to the emergency department from 17 May 2017 through 27 September 2017, triaged as category 1, 2 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 26 publications
(17 reference statements)
2
36
1
6
Order By: Relevance
“…The conventional MEWS has been applied for identifying mortality risk and determining trauma severity. The MEWS was previously reported to be an excellent predictor of in-hospital mortality because the MEWS achieves high area under ROC (AUROC ranges from 0.83 to 0.90 in Xie et al (2018) , Jiang, Jiang & Mao (2019) , and Smith et al, 2013 ), although the performance may decrease for elderly patients ( Mitsunaga et al, 2019 ). However, the performance of the MEWS in identifying injury severity is moderate (AUROC <0.8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional MEWS has been applied for identifying mortality risk and determining trauma severity. The MEWS was previously reported to be an excellent predictor of in-hospital mortality because the MEWS achieves high area under ROC (AUROC ranges from 0.83 to 0.90 in Xie et al (2018) , Jiang, Jiang & Mao (2019) , and Smith et al, 2013 ), although the performance may decrease for elderly patients ( Mitsunaga et al, 2019 ). However, the performance of the MEWS in identifying injury severity is moderate (AUROC <0.8).…”
Section: Discussionmentioning
confidence: 99%
“…Given the simplicity and speed required for tools to be effect in triaging multiple trauma patients in EDs, tools such as the modified early warning score (MEWS) (Bozkurt et al, 2015) have now been widely applied in EDs, particularly in China (Xie et al, 2018). The MEWS has been used for many purposes: to predict in-hospital mortality (Xie et al, 2018), determine hospital admission (Wei et al, 2019), identify critically ill patients (Kruisselbrink et al, 2016), and predict injury severity and need for ICU admission (Salottolo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…ED-based cardiac arrest was also associated with better neurological outcomes and a shorter length of hospital stay. 3,14 Efforts to identify patients who may progress to ED-based cardiac arrest have traditionally been approached through identification of critically ill patients through triage on arrival to the ED and the identification of patients who unexpectedly deteriorate during their stay in the ED. [15][16][17] Each of these approaches has significant limitations.…”
Section: Epidemiology Of Cardiac Arrest In the Emergency Departmentmentioning
confidence: 99%
“…[35][36][37][38] However, there is an increasing body of evidence that early warning scores may be useful in identifying patients at high risk of in-hospital mortality when used at triage. 14,[39][40][41] Of the numerous early warning scores, the Modified Early Warning Score, National Early Warning Score, and Rapid Emergency Medicine Score are the best studied in the ED. 42 The Modified Early Warning Score has the advantage of being the most studied early warning score in the ED.…”
Section: Aggregate-weighted Scores At Triagementioning
confidence: 99%
“…Previous studies have shown that triage levels were related to certain patient outcome variables, such as hospital admission, ICU admission and in-hospital mortality [2,[13][14][15]. Level 1, level 2 and level 3 are defined as urgent patients with a higher proportion of serious adverse events, such as hospital admission and mortality, compared with level 4, which is defined as non-urgent patients [13,16].…”
Section: Introductionmentioning
confidence: 99%